Skills and resourses that influence the business women - Escandón Barbosa, Diana; Arias Sandoval, Alberto (Cuadernos de Administración, 2011)
This article is aimed at trying to get to know the main competitive factors within companies created by Colombian women for which are analyzed data collected by GEM Colombia 2009, but filtering the database and allowing to use only the related to the female gender. Within the results will be able to obtain a model consistent with the literature on competitiveness, emphasizing human resources, innovation and internationalization. However, there is no evidence that explain each of these variables by gender and much less the relationship with competitiveness. For which, the authors pose a first approach and that can generate investigative trends in this regard. The methodology used in this article is a system of structural equations, through the statistical package SPSS Amos 18, which allows you to generate an outline of relations between the variables, and closer to the trends of models in the explanations of the social sciences.